Influence of Self-Monitoring on Intermittent Explosive Disorder among Female Inmates’ Violence Towards Male Partner in Selected Women Prisons, Kenya - Kaluai, Hellen Makena; K’Okul, Florence; Maroko, Mokua Gilbert (International Journal of Humanity and Social Sciences, 2025)
Purpose of this study was to evaluate the influence of one of the cognitive strategies that is: self-monitoring, on intermittent explosive disorder among female inmates’ violence towards male partners in selected women prisons, in Kenya. Methodology: The study was anchored on Social cognitive theory by Albert Bandura and self-evaluation maintenance theory by Abraham Tesser. The study used an Ex Post Facto research design. The study was carried out at Langata and Thika Women Prisons. Quantitative data was obtained from the sampled inmates using questionnaires; while qualitative data was collected using interview guides from the prison key informants. The study incorporated 8 constables, 4 counsellors, 3 chaplains as key informants. Stratified and proportionate simple random sampling was used to select a sample size of 307 inmates. Quantitative data was analyzed using both descriptive and inferential tests. Findings: There was a statistically non-significant negative relationship between self-monitoring and intermittent explosive disorder, [r (257) = -.114, p = .068]. This demonstrated that the increase in intensity of self-monitoring indicators, such as: identification of negative/positive thoughts; identifying the target behavior; focusing on tasks among the inmates; decreased the severity of intermittent explosive disorder thoughts and behavior such as: - rage, irritability, racing thoughts, violence, aggression, yelling and intimidation. Unique Contributions to Theory, Policy and Practice: Based on these findings, the study recommended prison management through the ministry of Interior and Coordination in Kenya to provide cognitive mindfulness interventions and positive counselling among female inmates on individual self-monitoring behavior towards male partners. Cognitive self-monitoring would provide solutions on inmates on post-traumatic stress, revitalize mental health to decrease violence. This would reduce women imprisonment; develop self-esteem for positive behavior change. The study findings would add knowledge to the practicing counsellors, prison stakeholders, policymakers and researchers on the use of self-monitoring as a tool of cognitive restructuring strategies in behaviour change.